The effectiveness of vestibular rehabilitation therapy vs conservative treatment on dizziness: a systematic review and meta-analysis. (3rd September 2019) - Luth, Carl; Bartell, Desiree; Bish, Michaela; Yudd, Andrew; Palaima, Mary; Cleland, Joshua A.
Abstract: Background: Dizziness is a common condition which may lead to loss of function and disability. Vestibular Rehabilitation Therapy (VRT) may be utilized to affect the vestibular system and reduce dizziness. However, controversy exists regarding the most effective interventions to treat dizziness. Objectives: To examine the effectiveness of VRT compared to other conservative treatments in reducing dizziness and disability. Methods: A literature search was performed using different combinations of the terms: dizziness, physical therapy, vertigo, vestibular, cervicogenic dizziness to identify randomized clinical trials comparing VRT to conservative treatments. The Cochrane Risk of Bias Tool was used to assess the quality of each included study. Additionally, a meta-analysis and qualitative analysis of the evidence was performed. Results: Ten studies were included in the systematic review. Only four studies were included in the meta-analysis due to lack of adequate data reported for continuous outcomes. Eight studies scored less than a 69% on the Cochrane risk of bias tool indicating a low to moderate risk of bias. The meta-analysis revealed that VRT was found to be more effective than conservative treatment for short term outcomes (0–3 weeks) but not long-term outcomes (4 or more weeks). The results from the studies excluded from the meta-analysis but included in the systematic review are inconclusive. Conclusions: VRT was only found to be more effective than other conservative treatments in the short term.